PENGELOLAAN AGROSILVOPASTURA DI DUSUN NAMAA NEGERI PELAUW PULAU HARUKU KABUPATEN MALUKU TENGAH - ANDRE TUHALAURUW; MERSIANA SAHUREKA; BILLY. B SEIPALLA (JURNAL HUTAN PULAU-PULAU KECIL, 2021)
This study aimed to determine the management pattern of agrosilvopasture by community and the factors that can affect the management of agrosilfopasture in Namaa Hamlet, Pelauw Village, Haruku Island, Central Maluku Regency. This research conducted by using purposive sampling method, with respondents as many as 20 heads of household. Primary and secondary data taken by observation and interviews related to respondent about the agrosilvopasture pattern. The data obtained were analyzed with a quantitative approach and qualitative descriptions. The results showed that the management of agrosilvopasura in Namaa Hamlet was carried out by combining agricultural, forestry and livestock crops. The stages of agrosilvopasture management carried out in the hamlet land consist of stages land preparation, procurement of seeds and planting, maintenance, harves and post harvest. The factors that influence the management of agrosilvopasture in Namaa Hamlet are divided into supporting factors and inhibiting factors. Supporting factors include the application of the agrosilvopasture pattern, local wisdom that is still being applied, the community is very dependent on the results of the agrosilvopasture, the group work system, the government assistance, the diversity of plant species, the results that are in demand by consumers and the diversity of livestock species. Inhibiting factors in agrosilvopasture management include limitations of agrosilvopasture product management technology, lack of knowledge of farmers and stakeholders about agrosilvopasture, not yet maximal assistance process, land use that has not been maximized, seed prices are too expensive, pests and diseases, marketing chain and local products that are less competitive.